A UNIFORM ARTIFICIAL INTELLIGENCE STATUTE - Świerczyński, Marek; Więckowski, Zbigniew (Zeszyty Prawnicze, 2023)
The paper presents recommendations for new legislation required for the definition of a uniform artificial intelligence statute, in other words, legislation to justify the need for, and the feasibility of determining the proper law for the broadest possible range of legal issues relating to artificial intelligence. The article starts with a discussion of the problem of the legal personality of artificial intelligence and the validity of the establishment of a personal statute for artificial intelligence. These considerations also take into account the public policy clause and other mechanisms to correct the designation of the proper law. Next, the article discusses a property-law statute for artificial intelligence, and ends with an analysis of the choice of connecting factors for the determination of a uniform statute of artificial intelligence.